Biological Control of the Coconut Hispine Beetle, Brontispa longissima Gestro (Coleoptera: Chrysomelidae) by the Parasitoid, Asecodes hispinarum Bouček (Hymenoptera: Eulophidae) on a Golf Course - Thitraporn Pundee,; Surachate Jamornmarn,; Wiboon Chongrattanameteekul,; Chalerm Sindhusake,; Amporn Winotai,; Rut Morakote, (Agriculture and Natural Resources, 2009)
The coconut hispine beetle, Brontispa longissima Gestro is an invasive pest in Southeast Asia.Since chemical control of the beetle is not recommended due to its high cost and risk to the environment, biological control is a desirable tool for effective control of this pest. This experiment was conducted at the Panya Indra golf course, Bangkok in 2007 using the parasitoid, Asecodes hispinarum Bouček, an effective larval parasitoid. The number of parasitoids released was based on the density of the damaged coconut trees. Continual releases were made in and around the area. Mummified larvae were counted once a month by selecting 20 infested spear leaves. The parasitoids were observed five months after release. The mummified larvae were collected in June, August and November and the percentage parasitized was found to be 13.48%, 8.58% and 14.08%, respectively. Severe, leaf damage levels decreased in December. The results showed that the new coconut palm leaves were fresh with less damage. A population study of B. longissima was also undertaken by randomly sampling 20 spear leaves. High and low population levels were observed from March to June and from July to December, respectively.